Am nevoie de rezolvare la punctul 1 pls
Anexe:
Răspunsuri la întrebare
Răspuns de
0
2x - y = 3 => x=(3+y)/2 =>
x² - 2xy + x - 4y = 3 ((3+y)/2)² - 2*(3+y)/2*y + (3+y)/2 - 4y = 3
x=(3+y)/2 => x=(3+y)/2 =>
(3+y)²/2-2y(3+y)+3+y-8y=6 -3y²/2-10y+9/2-3=0
x=(3+y)/2 x₁=(-1-√109)/6
y₁=(-10+√109)/3 => x₂=(√109-1)/6
y₂=(√109-10)/3 y₁=(-10+√109)/3
y₂=(√109-10)/3
x² - 2xy + x - 4y = 3 ((3+y)/2)² - 2*(3+y)/2*y + (3+y)/2 - 4y = 3
x=(3+y)/2 => x=(3+y)/2 =>
(3+y)²/2-2y(3+y)+3+y-8y=6 -3y²/2-10y+9/2-3=0
x=(3+y)/2 x₁=(-1-√109)/6
y₁=(-10+√109)/3 => x₂=(√109-1)/6
y₂=(√109-10)/3 y₁=(-10+√109)/3
y₂=(√109-10)/3
Alte întrebări interesante
Matematică,
8 ani în urmă
Chimie,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă